2020
DOI: 10.3390/jof6020069
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutritive Value of Purple Field Corn Residue and Rice Straw by Culturing with White-Rot Fungi

Abstract: It was hypothesized that white-rot fungus fermented with rice straw and purple field corn improves nutrient utilization via enhanced digestibility and lowers methane (CH4) production due to the effects of the lovastatin compound. The aim of the current experiment was to investigate the effect of inoculation of two fungi belonging to white-rot fungus type on feed value and ruminal fermentation characteristic. The experiment was carried out according to a completely randomized 3 × 3 factorial design: three rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
6
30
1
Order By: Relevance
“…Methyl coenzyme-M reductase (mcr) is the key enzyme in the methanogenesis process [5,41]. These results were supported by our previous in vitro test, which showed that fermenting roughage with P. ostreatus and V. volvacea significantly reduced CH 4 production by approximately 10.83% to 11.32% compared to the untreated substrates [12]. Likewise, Jahromi [14] reported that lovastatin in fermented rice straw is effective at suppressing 96.43% of the CH 4 emission.…”
Section: Volatile Fatty Acid Profile and Ch 4 Productionmentioning
confidence: 60%
See 3 more Smart Citations
“…Methyl coenzyme-M reductase (mcr) is the key enzyme in the methanogenesis process [5,41]. These results were supported by our previous in vitro test, which showed that fermenting roughage with P. ostreatus and V. volvacea significantly reduced CH 4 production by approximately 10.83% to 11.32% compared to the untreated substrates [12]. Likewise, Jahromi [14] reported that lovastatin in fermented rice straw is effective at suppressing 96.43% of the CH 4 emission.…”
Section: Volatile Fatty Acid Profile and Ch 4 Productionmentioning
confidence: 60%
“…Hristov et al [42] demonstrated that protein could degrade into NH 3 -N by microbial extracellular enzymes and deamination. Likewise, a previous report indicated that NH 3 -N was increased by roughage fermented with white rot as compared with a control in vitro [12]. Moreover, the high NH 3 -N concentration in the roughage fermented with P. ostreatus was probably influenced by the high CP level, which is a supplemental source of N. In addition, P. ostreatus and V. volvacea are composed of CP, and there is a probability of additional protein supply to the cattle.…”
Section: Ruminal Characteristics Microbial Count and Blood Metabolitementioning
confidence: 61%
See 2 more Smart Citations
“…presenting a conservative case with respect to bioethanol production. Purple corn stover hybrids with higher structural carbohydrate content have been reported 26,27 . Thus, the effect of low (LSC) and high structural carbohydrate content (HSC) on MESP of the modified processes was evaluated (Table 7).…”
Section: Resultsmentioning
confidence: 99%